Analisis Pengendalian Biaya dan Waktu Dengan Metode Nilai Hasil Pada Pembangunan Jalan Simpang Empat Gedung Baru Universitas Palangka Raya - Grace Maria Christy; Veronika Happy Puspasari; Waluyo Nuswantoro (Universitas Islam 45, 2023)
The construction of the four-way intersection of the Peat Science and Technology Development Center and Peat Innovation Building and Yos Sudarso's Merah Putih Building is an effort to develop facilities and infrastructure that function as the main gate of the University of Palangka Raya. In its implementation until the 7th week it is not yet known which irregularities have occurred. This study aims to analyze cost and time control to detect if there is inefficient performance in project completion. The Result Value Method was developed for this study. The Cost Performance Index (CPI) for the seventh week was 1.11 > 1, and the Schedule Performance Index (SPI) was 1.07 > 1. Estimates for the remaining work came in at IDR 979,624,988, with a final total cost of IDR 2,228,446,288 being calculated. The estimated time for the remaining work based on calculations by the Yield Value Method until week 7 is 53 days and the estimated total time for project completion is 102 days. So it can be concluded that the estimated time for completion of the project is 3 days faster than the planning process.